2021
DOI: 10.3390/geriatrics6010019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Emerging Technologies to Meet the Care and Support Needs of Older People: A Delphi Survey

Abstract: Some emerging technologies have potential to address older people’s care and support needs. However, there is still a gap in the knowledge on the potential uses of these technologies in some care domains. Therefore, a two-round Delphi survey was conducted to establish a consensus of opinion from a group of health and social technology experts (n = 21) on the potential of 10 emerging technologies to meet older people’s needs in five care and support domains. Experts were also asked to provide reasons for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
(130 reference statements)
0
16
0
Order By: Relevance
“…Of the 26 studies, 3 (12%) studies highlighted the advantage of AI being constantly available without restrictions such as physical location, time, and access to a structured treatment [ 24 , 30 , 38 ]; 3 (12%) other studies also mentioned the appreciation of respondents for how an AI system could collect data remotely in a nonintrusive and user-friendly manner [ 23 , 24 , 28 ]. These studies mostly represented the perceptions of consumers and health care providers [ 24 , 30 , 38 ] ( Multimedia Appendix 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 26 studies, 3 (12%) studies highlighted the advantage of AI being constantly available without restrictions such as physical location, time, and access to a structured treatment [ 24 , 30 , 38 ]; 3 (12%) other studies also mentioned the appreciation of respondents for how an AI system could collect data remotely in a nonintrusive and user-friendly manner [ 23 , 24 , 28 ]. These studies mostly represented the perceptions of consumers and health care providers [ 24 , 30 , 38 ] ( Multimedia Appendix 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This could be related to concerns over the lack of integration and synthesis of information from various sources, standardization of data collection, and the overall sustainability of AI-assisted health care service delivery [ 40 , 45 ]. However, 8% (2/26) of studies reported that respondents had similar trust in AI as compared with a human physician’s diagnoses [ 28 , 45 ]. Possible mitigation strategies include increasing system transparency and reporting system accuracies [ 26 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, wearable robotics have been tried in patients with spinal cord injury ( Chisholm et al, 2016 ; Gagnon et al, 2019 ), multiple sclerosis ( Drużbicki et al, 2021 ), stroke ( Singh et al, 2021 ), osteoarthritis ( McGibbon et al, 2021 ; Papi et al, 2016 ), and robotic assistive devices are being developed and deployed with older adults ( Verrusio et al, 2018 ) among others. A recent Delphi survey about emerging technologies for older adult care also identified informal carers as a population that could benefit from the use of exoskeletons, given the hands on role they play in providing care for loved ones who are chronically unwell or terminally ill ( Abdi et al, 2021 ). Hence, nurses could work with carers when discharging patients from hospital or assessing their home care needs in the community, to determine if a wearable robot could support family members in their day-to-day caring roles.…”
mentioning
confidence: 99%